2014
DOI: 10.1016/j.acra.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subchondral Bone Marrow Lipids of Acute Anterior Cruciate Ligament (ACL)-Injured Patients at 3 T

Abstract: Rationale and Objectives The objectives of this study were to investigate the changes in compartment-specific subchondral bone marrow lipids of femoral–tibial bone in acute anterior cruciate ligament (ACL)-injured patients compared to that of healthy volunteers and patients with osteoarthritis (OA) (Kellgren–Lawrence [KL] grade 2–3). Materials and Methods A total of 55 subjects were recruited in the study and subdivided into three subgroups: 17 healthy controls (4 females, 13 males; mean age = 41 ± 16, age r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Despite this, Li et al [12] and Wang et al's more recent study [21] interestingly both observed ACL-injured knees to have a higher UI than their OA counterparts, suggesting the possibility of different biochemical changes occurring within ACL and OA BMEL. This study saw a non-significant increase and decrease in UI in the BMEL and non-BMEL regions of ACL-injured knees compared to those with OA, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite this, Li et al [12] and Wang et al's more recent study [21] interestingly both observed ACL-injured knees to have a higher UI than their OA counterparts, suggesting the possibility of different biochemical changes occurring within ACL and OA BMEL. This study saw a non-significant increase and decrease in UI in the BMEL and non-BMEL regions of ACL-injured knees compared to those with OA, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…These results are congruent with observations from a previous cross-sectional study [12] and indicate pathological changes in bone marrow within BMEL regions. One study conducted by Wang et al [15] found a general decrease in UI in subjects with mild OA compared to control, and another [21] found no significant differences in UI between ACL-injured and control knees or between OA and control knees. However, Wang et al's studies employed single-voxel MRS and focused on the UI of different compartments within the knee joint as opposed to BMEL and non-BMEL regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous MR studies have demonstrated alterations in microstructural trabecular morphometry measurements between volunteers and individuals with OA [13,14], and that such measurements correlate well with severity of OA [15]. Proposed mechanisms of alteration in SB architecture include entry of inflammatory infiltrates via vascular channels in the SB [37] and increased deposition of subchondral marrow lipids [38].…”
Section: Discussionmentioning
confidence: 97%
“…Only a few studies have assessed the use of MRS for BM of the knee. 32,59,61,62 The value of MRS for subchondral BM after cartilage repair surgery has not been studied.…”
mentioning
confidence: 99%